2021
DOI: 10.1021/acs.langmuir.1c01559
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Water Nucleation and Growth Based on Microdroplet Mobility on Lubricant-Infused Surfaces

Abstract: Lubricant-infused surfaces (LISs) can promote stable dropwise condensation and improve heat transfer rates due to a low nucleation free-energy barrier and high droplet mobility. Recent studies showed that oil menisci surrounding condensate microdroplets form distinct oil-rich and oil-poor regions. These topographical differences in the oil surface cause water microdroplets to rigorously self-propel long distances, continuously redistributing the oil film and potentially refreshing the surface for re-nucleation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…Results revealed the larger microdroplet nucleation rate density in the oil-poor region, as shown in dashed red rectangle in Fig. 11(a), as a consequence of the reduced thermal conduction resistance imposed by the thinner oil film and the lower oil-air interfacial temperature preferential for nucleation [173,174] , which has also been demonstrated in the recent work of Sun et al [175] . Then droplets remained stationary growing through direct condensation at the nucleation sites and once they reached certain size the droplets suddenly coalesced with neighboring ones, as shown in Fig.…”
Section: Condensation On Uniformly Structured Slipsssupporting
confidence: 71%
“…Results revealed the larger microdroplet nucleation rate density in the oil-poor region, as shown in dashed red rectangle in Fig. 11(a), as a consequence of the reduced thermal conduction resistance imposed by the thinner oil film and the lower oil-air interfacial temperature preferential for nucleation [173,174] , which has also been demonstrated in the recent work of Sun et al [175] . Then droplets remained stationary growing through direct condensation at the nucleation sites and once they reached certain size the droplets suddenly coalesced with neighboring ones, as shown in Fig.…”
Section: Condensation On Uniformly Structured Slipsssupporting
confidence: 71%
“…In Video 4 from the Supplemental Material, a ≈600-µm water droplet was left on the surface from previous condensation and coalescence events. At this relatively high vapor-substrate temperature difference (≈30°C), nucleation occurs not only in the thin film region in-between larger droplets, socalled oil-poor regions 11 , but also on the oil menisci themselves. The outward interfacial Marangoni flow can radially distribute these meniscus-nucleated droplets to regions further away from the central droplet, i.e., towards oil-poor regions.…”
Section: Influence Of Bidirectional Droplet Propulsion On Dropwise Co...mentioning
confidence: 99%
“…Meniscus-mediated behaviors of droplets or particles can also easily be observed in our daily life, such as the cheerios effect, where cereals tend to aggregate and form rafts 5 , bubble clusters near the walls of sodafilled glasses, and oil drops floating on a bowl of water that migrate away from the solid wall 6 . Meniscusclimbing mechanisms have also been discovered and used for micro/nano-particle self-assembly 7 and enhanced water harvesting [8][9][10][11] . Manipulating small objects at liquid interfaces is furthermore becoming increasingly important in areas of microfluidics [12][13][14][15] , microrobotics 16 , and biological sensing and testing 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Liquid infused surfaces (LIS) have been shown to enhance droplet mobility in condensation applications, by dramatically reducing contact angle hysteresis, however the gradual loss of lubricant could make the effect short lived. [31,[36][37][38][39] Polymer infused porous surfaces also offer low contact angle hysteresis and tunability, as well as being more robust than LIS, however they are complex to fabricate and may be challenging to scale up. [37] Only recently, Cha et al have shown that a less complex hydrophilic surface with low contact angle hysteresis, can determine efficient dropwise condensation.…”
Section: Introductionmentioning
confidence: 99%